The History of Notions and Ideas in the Works of Emanuel Rádl - Pazderský, Roman (Dějiny – teorie – kritika, 2014)
The text is a collection of several brief observations and considerations which deal with Emanuel Rádl (1873–1942), an important Czech philosopher, and his contribution to Czech scholarship in the area of history of ideas. The text opens with a brief contextualisation of Rádl’s work within the general milieu of Czech intellectual life of the fi rst half of the twentieth century. Then the author traces Rádl’s role in highlighting the importance of terminology in contemporary Czech interdisciplinary discourse, especially in the so-called ‘struggle for the meaning of Czech history’, where Rádl’s views are compared, among others, to those of Mendl, Slavík, and Pekař. In the second part of the contribution, the author analyses Rádl’s original approach to the history of ideas using the example of his two most important works, which focus on the history of thought in natural science (Dějiny vývojových teorií v biologii [The History of Evolutionary Theories], Prague 1909) and in social science (Dějiny filosofie [A History of Philosophy], Prague 1932–1933). This analysis demonstrates that though Rádl’s link to this, at that time nascent and not yet fully established, scientific field was only implicit, this philosopher ought to be seen as one of the foremost pioneers of the history ideas and history of thought in the Czech intellectual environment. The conclusion offers some brief thoughts on the relevance of Rádl’s intellectual legacy especially in the still hotly debated field of possible theoretical and methodological links between natural science and humanities, especially the historical science.